The Mediating Role of Self - Efficacy on Students’ Entrepreneurship Education and Entrepreneurship Intention in Buea Municipality - Enongene, Gabriel Nnoko; Isoh, Alain Vilard Ndi (Business Management and Strategy, 2024)
The study on the effect of entrepreneurship education on students’ Entrepreneurial intentions has been of interest to researchers and continues to animate debate amongst scholars. This study aimed to investigate the mediating role of entrepreneurial self-efficacy on the impact of entrepreneurship education on university students' entrepreneurial intentions in Buea municipality. The researchers adopted a cross sectional descriptive survey design and quantitative data was collected from a sample of 300 university students in Buea Municipality. The study employed SPSS and Amos software to ascertain the effect of entrepreneurship education, self-efficacy and personal background factors on entrepreneurial intentions. The theoretical framework developed was supported by the data through fit indices, reliability and validity from the valid responses. The findings of this study revealed that entrepreneurship education and self-efficacy have positive and significant effects on entrepreneurial intentions while personal background factors had a positive but insignificant effect on entrepreneurial intentions. Entrepreneurship education inserted the highest effect, followed by self-efficacy. The findings collaborated the theory of planned Behaviour which argued that behaviours can be influenced through certain planned actions and are positively related to the entrepreneurial intentions of the student. The study recommends that universities could pay greater attentions to provide more practical entrepreneurship education and encourage students who show signs of entrepreneurial efficacy.